GE_GERICHTE P/20091/2020 vom 6. August 2024 - GE Cour de justice (2024)
PERQUISITION DE DOCUMENTS ET ENREGISTREMENTS;MESURE PROVISIONNELLE;SCELLÉS;DÉCISION D'IRRECEVABILITÉ;SÉQUESTRE(MESURE PROVISIONNELLE) | CPP.393.al1.leta; CPP.196; CPP.197